2014
DOI: 10.1128/iai.01434-13
|View full text |Cite
|
Sign up to set email alerts
|

Filifactor alocis Infection and Inflammatory Responses in the Mouse Subcutaneous Chamber Model

Abstract: dRecent microbiome studies have implicated a role for Filifactor alocis in periodontal disease. In this study, we investigated the colonization and survival properties of F. alocis in a mouse subcutaneous chamber model of infection and characterized host innate immune responses. An infection of 10 9 F. alocis successfully colonized all chambers; however, the infection was cleared after 72 h. F. alocis elicited a local inflammatory response with neutrophils recruited into the chambers at 2 h postinfection along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 48 publications
1
53
0
Order By: Relevance
“…The rpoN gene (PGN_1202, 33277; PG1105, W83 orthologue; PGTDC60_1103, TDC60 orthologue), for example, encodes the alternative sigma factor, σ 54 . Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The rpoN gene (PGN_1202, 33277; PG1105, W83 orthologue; PGTDC60_1103, TDC60 orthologue), for example, encodes the alternative sigma factor, σ 54 . Bacteroides spp.…”
Section: Discussionmentioning
confidence: 99%
“…In a mouse model, it has been shown that T. denticola has an ability to disseminate to distant sites from the site of infection [246]. In a mouse subcutaneous model, it has been shown that the newly emerging periodontal pathogen, F. alocis has the ability to colonize and spread to distant sites [54].…”
Section: Periodontal Diseases and Gdmmentioning
confidence: 99%
See 3 more Smart Citations